PENERAPAN KEPEMIMPINAN TRANSFORMATIF OLEH KEPALA SEKOLAH DI SD NEGERI 057224 PALUH GUSTA KABUPATEN LANGKAT - Nuraida Nuraida (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
The purpose of this research is: Describing the actualization of the principal's imaginary impact at SD Negeri 057224 Pluh Gusta in Langkat Regency. This kind of investigation is a qualitative detail study. using a phenomenological strategy. Through observation, conversation, and recording, data were collected. Data reduction, data presentation, conclusion drawing, and substantiation techniques were used to evaluate the data. Through credibility tests that included member checks and triangulation of methods (source, methodology, and time), the veracity of the data was checked. The findings of this study indicate that, although the implementation of the influence of the principal's idealization in SD Negeri 057224 Paluh Gusta in Langkat Regency, namely the participation of teachers and staff in the administration of meetings, providing ideas and opinions, and forming teams. developing a vision and mission, has not been optimal for teacher self-development.